GROWTH DYNAMICS OF INTERCROPPING SYSTEM IN CASTOR (RICINUS COMMUNIS L.) UNDER IRRIGATED ECOSYSTEM - AGARWAL, S.K.; PORWAL, M.K. (Annals of Agricultural Research, 2014)
A field experiment was conducted to select suitable method of planting and intercropping with castor. Paired row planting of castor (60/120 cm x 60 cm) significantly improved the growth parameters (plant height, DMA, CGR, NAR, LAI), yield attribute (branches plant-1, length of primary spike, capsule plant-1, seed weight plant-1, 100 seed weight) and the yields (seed, stalk and biological). Significantly higher values of growth parameters (plant height at harvest, DMA at 70, 120 and 180 DAS, CGR between 40-70 DAS and 70-120 DAS, LAI and yield attributes were recorded under paired planting of castor with greengram followed by castor+blackgram and castor+clusterbean. Maximum total seed yield and also stalk and biological yields of castor were recorded under castor+greengram intercropping system which was significantly higher over castor+ sesame intercropping system. Significantly higher castor equivalent yield (49.55 q ha-1) was realised under castor+greengram intercropping system over castor+ clusterbean and castor+sesame but found at par with castor+blackgram.